Use of an image intensifier for the localization and removal of a foreign body in the lower lip - Mulinari-Santos, Gabriel; Bonardi, João Paulo; Fabris, André Luís da Silva; Puttini, Igor de Oliveira; Coléte, Juliana Zorzi; Duailibe-de-Deus, Ciro Borges; Faverani, Leonardo Perez; Garcia Júnior, Idelmo Rangel; Souza, Francisley Ávila (ARCHIVES OF HEALTH INVESTIGATION, 2018)
Foreign bodies can be found in the soft tissues of the face and in the maxillary bones in routine radiographic examinations. In the majority they do not present symptomatology. The removal of foreign bodies without the accurate location can cause severe complications. We present a case of 44-year-old male complaining an unusual foreign body in the lower lip region. Radiography did not reveal the exact location, and did not let a resolution at first time. Subsequently, the surgical treatment was effective with the aid of navigation-assisted fluoroscopy that showed the precise location of the foreign body for removal and avoided more discomfort to the patient. Descriptors: Foreign Bodies; Fluoroscopy; Traumatology.